Prioratization of villages for providing safe water sources in disaster prone Sarankhola Upazila of Bagerhat district: a GIS based approach - Sultana, Sarmin; Alam, Md Badrul; Ahmed, Kazi Matin (Bangladesh Journal of Scientific Research, 2014)
Sarankhola Upazila of Bagerhat district is one of the most water scarce and disaster prone areas of the country. Village level map of existing safe water options for this Upazila has been prepared using data on number of water supply technologies for each village using ArcGIS 9.1. Hydrometeorological, geological and hydrogeological data have been analyzed to decipher the geohydro-environment in order to validate site specific water supply options. Existence of different safe water options in every village alongside population density has been presented in the map in order to identify high, medium and low priority areas. It is evident from the analysis that where shallow tubewell is less successful, the safe water coverage is also low. Rainwater harvesting is the least used option despite having high annual rainfall and therefore, can be used in large numbers along with pond sand filter (PSF) in order to improve safe water coverage. Results obtained from the study can be utilized as a planning tool to optimize the safe water coverage by targeting priority areas. The map also identifies the areas suitable for a particular safe water option and can be used as a guiding tool for installing the appropriate sustainable safe water options during future interventions. DOI: http://dx.doi.org/10.3329/bjsr.v26i1-2.20226 Bangladesh J. Sci. Res. 26(1-2): 11-19, December-2013